2009
DOI: 10.1152/japplphysiol.00083.2009
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical effects of obesity on airway responsiveness in otherwise healthy humans

Abstract: We investigated whether obesity is associated with airway hyperresponsiveness in otherwise healthy humans and, if so, whether this correlates with a restrictive lung function pattern or a decreased number of sighs at rest and/or during walking. Lung function was studied before and after inhaling methacholine (MCh) in 41 healthy subjects with body mass index ranging from 20 to 56. Breathing pattern was assessed during a 60-min rest period and a 30-min walk. The dose of MCh that produced a 50% decrease in the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 50 publications
(74 reference statements)
4
42
0
4
Order By: Relevance
“…Obesity may also reduce airway caliber 30 , allowing a greater increase in resistance for a given absolute reduction in airway diameter and manifesting as increased airway reactivity. Data from healthy subjects suggested that airway reactivity is inversely correlated with BMI 33 . Others have suggested that asthma severity in obesity is affected by altered levels of adipokines and inflammatory cytokines 34,35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity may also reduce airway caliber 30 , allowing a greater increase in resistance for a given absolute reduction in airway diameter and manifesting as increased airway reactivity. Data from healthy subjects suggested that airway reactivity is inversely correlated with BMI 33 . Others have suggested that asthma severity in obesity is affected by altered levels of adipokines and inflammatory cytokines 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…One might hypothesize that very mild asthmatics would behave like non-asthmatic subjects. However, data concerning the relationship between obesity and airway hyperreactivity in otherwise healthy subjects are conflicting, with some studies supporting an association 33,40,4447 and others not 7,39,41,48 .…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of both obesity and asthma has increased worldwide in recent years, and obesity has been implicated as a risk factor for asthma and as a predisposing factor for airway hyperresponsiveness (AHR) (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…The shear modulus of the lung has been estimated by indenting the pleural surface of the lung inflated to variety of transpulmonary pressures and measuring the surface indentation as a function of the applied force (28, 45). The dimensions of the bulk and shear moduli are the same as for pressure (force per unit area) and the results show a value for the shear modulus of ~0.7Ptp, while the bulk modulus ranges from 3Ptp to 7Ptp as the lung volume changes from 20% to 80% of the total lung capacity (43, 77). This means that it is much easier to distort lung’s shape than to inflate the lung.…”
Section: Continuum Mechanics Analysismentioning
confidence: 99%
“…As mentioned above, breathing at low lung volume increases airway responsiveness in normal individuals (20) and could contribute to the airway hyperresponsiveness in obese individuals. Torchio et al found linear relationships between body mass index and measures of airway sensitivity (PD50) and maximal response to inhaled methacholine; more obese individuals required a lower dose to produce the airway narrowing and their maximal achievable airway narrowing was greater (77). This issue, however, is still unsettled, as evidenced by a recent study from Salome et al, who found no difference in airway sensitivity or maximal response in a direct comparison of obese and non-obese normal subjects (69).…”
Section: Interdependence In Pathologic Situationsmentioning
confidence: 99%